This article is about some lexical work in newspaper «Al-Ahram» (Journal of Oriental Studies, 2017)
The article considers semantic structural peculiarities of political termsand the way of their formation, the questions of their adequate use age inaccordance to the demands of the contemporary time in the frame of arabbiography, general linguistics and the questions of the influence of globalprocess to term formation , published in the article “Al-Ahram” newspaper.